Analysis of determinant factors with the severity of COVID-19 in pregnancy - Yanti Linda; Sekarini Ni Nyoman Ayu Desy; Susanti Dwi (BIO Web of Conferences)
In Indonesia as well as other countries, pregnant women are considerably more likely to have COVID-19. According to data, 1.3% of pregnant women with the infection needed mechanical breathing and intensive care unit treatment. The purpose of this study was to ascertain the association between the severity of COVID-19 in pregnant women and variables such age, gestational age, blood type, immunization status, and comorbidities. 40 pregnant women having a COVID-19 diagnosis between 2021 and 2023 were sampled for a correlational study design at a Lampung hospital. The Pearson correlation test was utilized for data analysis. The findings demonstrated a significant relationship between COVID-19 severity and gestational age, blood type, and immunization status (p-value <0.05). On the other hand, there was no statistically significant correlation between maternal age and comorbidities (p-value >0.05). Early gestational age, certain blood types (A, B, and AB), and immunization status are important factors impacting the severity of COVID-19 in pregnant women, according to the study’s findings. In order to lessen the severity of COVID-19, health care practitioners are urged to ensure that pregnant women receive vaccinations and to provide close monitoring during the first trimester of pregnancy, particularly for those with blood types A, B, or AB.